PENERAPAN TEKNIK AKUPRESUR TERHADAP PENURUNAN NYERI PASCA OPERASI SECTIO CAESAREA - Nur Insani Muslimah; Diah Nur Anisa (JOURNAL SAINS STUDENT RESEARCH, 2026)
Post-cesarean section (CS) pain is a common problem experienced by mothers due to tissue trauma at the surgical incision site. Unmanaged pain can hinder early mobilization, the breastfeeding process, and slow the patient’s recovery. One non-pharmacological therapy that can be used to help reduce pain is acupressure. The purpose of this study is to describe the application of acupressure therapy in reducing pain intensity in post-cesarean section patients. This study employed a descriptive case study method using a nursing process approach on a post-cesarean section patient at ‘Aisyiyah Muntilan Hospital. The intervention consisted of acupressure therapy applied to the LI4 and P6 points on the hands and the SP6 point on the inner side of the foot for 15–20 minutes, administered in the morning and afternoon for two consecutive days. Evaluation was conducted using the Numeric Rating Scale (NRS). Following the application of acupressure therapy, there was a reduction in pain intensity from a score of 6 to 5 on the first day and further decreased to a score of 3 on the second day. The application of acupressure techniques in post-cesarean section patients can help reduce pain intensity, enhance relaxation, and provide comfort during the recovery period. Acupressure techniques can serve as an effective, safe, and easily implemented nonpharmacological nursing intervention in the management of pain in post-cesarean section patients.